2007
DOI: 10.1007/s10555-007-9098-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase metabolism: roles in tumor progression and survival

Abstract: The metabolism of arachidonic acid through lipoxygenase pathways leads to the generation of various biologically active eicosanoids. The expression of these enzymes vary throughout the progression of various cancers, and thereby they have been shown to regulate aspects of tumor development. Substantial evidence supports a functional role for lipoxygenase-catalyzed arachidonic and linoleic acid metabolism in cancer development. Pharmacologic and natural inhibitors of lipoxygenases have been shown to suppress ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
209
1
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(227 citation statements)
references
References 140 publications
(162 reference statements)
2
209
1
15
Order By: Relevance
“…For example, it has been shown that LTB4, the major product of 5-LOX, is capable of recruiting and enhancing the activity of potential anti-tumor effector immune cells at the site of tumor development. However, other studies suggest that LOX products may prevent the anti-tumor immune response and thereby actively enhance tolerance to tumors (Pidgeon et al, 2007). Future studies will define which bioactive LOX products affect the responses of the immune system into elimination or tolerance of tumors.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…For example, it has been shown that LTB4, the major product of 5-LOX, is capable of recruiting and enhancing the activity of potential anti-tumor effector immune cells at the site of tumor development. However, other studies suggest that LOX products may prevent the anti-tumor immune response and thereby actively enhance tolerance to tumors (Pidgeon et al, 2007). Future studies will define which bioactive LOX products affect the responses of the immune system into elimination or tolerance of tumors.…”
mentioning
confidence: 99%
“…Among the LOX family, the 5-LOX isoform has been shown to be involved in tumorigenesis, as its inhibition blocks proliferation of a wide variety of tumoral cells, including lymphoid and myeloid cancer cells (Pidgeon et al, 2007). We found that NPM-ALK( þ ) ALCLs overexpressed 5-LOX (Figure 4a), as already shown for other cancers (Pidgeon et al, 2007;Radmark et al, 2007). The NPM-ALK-dependent increase in 5-LOX required ALK activity in lymphoid cells (Supplementary Figure 1a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8 15-Lipoxygenase-1 (15-LO-1) is a multifunctional enzyme able to produce a vast number of metabolites with diverse bioactivities. 9 Its expression has been demonstrated to be significantly decreased in several cancers, including breast, bladder, colon, skin and lung carcinomas. 10 A recent report by Viita et al 11,12 demonstrated that 15-LO-1 is able to prevent vascular endothelial growth factor-A-induced neovascularisation in rabbit eyes and skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%